A companion to American legal history - Hadden, Sally E.; Brophy, Alfred L. (Chicester : John Wiley & Sons, 2013)
A Companion to American Legal History presents a compilation of the most recent writings from leading scholars on American legal history from the colonial era through the late twentieth century. Presents up-to-date research describing the key debates in American legal historyReflects the current state of American legal history research and points readers in the direction of future researchRepresents an ideal companion for graduate and law students seeking an introduction to the field, the key questions, and future research ideas.
Introduction / Sally E Hadden, Alfred L Brophy -- Chronological overviews. Reconsidering the seventeenth century: legal history in the Americas / Elizabeth Dale -- What's done and undone: Colonial American legal history, 1700-1775 / Sally E Hadden -- 1775-1815 / Ellen Holmes Pearson -- The antebellum era through Civil War / Alfred L Brophy -- Beyond classical legal thought: law and governance in postbellum America, 1865-1920 / Roman J Hoyos -- American legal history, 1920-1970 / Christopher W Schmidt -- Individuals and groups. Native Americans / Christian McMillen -- African Americans in slavery / Thomas J Davis -- African Americans in freedom / James Campbell -- Women's legal history / Felice Batlan -- Families / David S Tanenhaus -- Who belongs? Immigrants and the law in American history / Allison Brownell Tirres -- The legal profession / Mark E Steiner -- Subject areas. Law and the economy of Early America: markets, institutions of exchange, and labor / Christine Desan -- Law and the economy in the United States, 1820-2000 / Harwell Wells -- Law and labor in the nineteenth and twentieth centuries / Deborah Dinner -- Siting the legal history of poverty: below, above, and amidst / Felicia Kornbluh, Karen Tani -- Taxes / Robin L Einhorn -- Law and the administrative state / Joanna L Grisinger -- Law and religion / Steven K Green -- Legal history and the military / Elizabeth L Hillman -- Criminal law and justice in America / Elizabeth Dale -- Intellectual property / Steven Wilf -- Legal thought. Law and literature / Jeannine Marie DeLombard -- Legal thought from Blackstone to Kent and Story / Steven J Macias -- American jurisprudence in the nineteenth and early twentieth centuries / James D Schmidt -- Critical legal studies / John Henry Schlegel -- The international context: an imperial perspective on American legal history / Clara Altman -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Law -- United States -- History; Law -- United States -- History; LAW -- Administrative Law & Regulatory Practice; Law; United States; Electronic books; History